PVP-assisted enhancement in ion storage performance of sol-gel derived nano-structured NiCo2O4 thin films as battery-type electrode. (March 2018) - Behzad, H.; Ghodsi, F.E.
Graphical abstract: Highlights: Polyvinylpyrrolidone was used to increase the porosity of the sol-gel derived nickel-cobaltite thin films for the first time. Polymer content of the films was completely degraded during the heating process. Increase of porosity significantly improved the electrochemical ion storage performance of the fabricated thin films. Polymer content of the solutions was optimized to obtain the maximum electrochemical capacity. Abstract: NiCo2 O4 thin films were successfully deposited on glass and ITO substrates by sol-gel method. In order to improve the electrochemical ion storage performance, different amounts of polyvinylpyrrolidone (PVP) were added to the solutions as porogen agent, which was totally degraded during the post-annealing process at 500 °C, as confirmed by Fourier transform infrared (FTIR) spectroscopy. The electrode with about 0.07 g/cm 3 PVP content in the solution, exhibited 65% higher specific capacity comparing with the electrode fabricated without PVP, due to significant nano-sized porosity remained after degradation of polymer chains, as displayed by field emission scanning electron micrographs (FESEM) of the surface and cross section of the samples. Also the electrochemical measurements in 1 M KOH aqueous electrolyte revealed the ion storage mechanism of the fabricated samples is battery-type.